12th AIAA Aviation Technology, Integration, and Operations (ATIO) Conference and 14th AIAA/ISSMO Multidisciplinary Analysis And 2012
DOI: 10.2514/6.2012-5404
|View full text |Cite
|
Sign up to set email alerts
|

Air Vehicle Design and Technology Considerations for an Electric VTOL Metro-Regional Public Transportation System

Abstract: This paper examines the potential of VTOL aircraft to supplement commuter rail services in a metropolitan or regional transportation system. An interdisciplinary study was conducted to examine the feasibility of integrating an aerial transport system into the existing airspace using a fleet of electrically powered rotorcraft. A notional network of stations and overall operating schedule were constructed based on the existing regional rail networks serving the San Francisco Bay Area. To define the VTOL vehicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The performance (efficiency) of a battery depends on the rate of discharge, which varies throughout the mission. Many analyses neglect battery efficiency or assume values of 98% or greater [10,134,155,156]. This implies that the rate of discharge has no impact on battery performance, which is fundamentally incorrect.…”
Section: Battery Specification and Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance (efficiency) of a battery depends on the rate of discharge, which varies throughout the mission. Many analyses neglect battery efficiency or assume values of 98% or greater [10,134,155,156]. This implies that the rate of discharge has no impact on battery performance, which is fundamentally incorrect.…”
Section: Battery Specification and Operationmentioning
confidence: 99%
“…The name of this motor type can be misleading, as the power supply is DC, but a DC/AC inverter (controller) allows for variable frequency AC motor operation. Not using brushes or commutators has many benefits, including less maintenance, higher reliability, and the ability to operate in reverse The electric motor weight is scaled with shaft power, with HTS motors having more favorable scaling exponents[134,135]. The motors and electrical system are sized for takeoff, which is the most power demanding condition.…”
mentioning
confidence: 99%
“…Because VTOL aircraft are an energy-intensive transportation mode for short distances, higher propulsion, and high-capacity battery technology was identified as two critical enablers to overcome current challenges with civil VTOL aircraft (German et al, 2013;Sinsay et al, 2012;Warwick, 2014). In consideration of current technological trend, the electric powered VTOL aircraft designs were foreseen to be available by 2030 (Young et al, 2011;Wang, Hou, Guo, & Gao, 2015).…”
Section: Civil Vtol Technologymentioning
confidence: 99%
“…While previous studies have shown that VTOL has the potential to improve airspace performance in capacity and delay based on an integrated fleet concept of operations, integrating VTOL aircraft into conventional airspace will be a complex issue. The study on VTOL mass transit feasibility jointly studied by NASA and Stanford (Sinsay et al, 2012) presented a conceptual design of an electric VTOL public transit system and network models using the existing railways and bus networks in the San Francisco metropolitan area. The simulations of a 30 seater VTOL operations carrying up to 30,000 passengers a day connecting eight potential multi-modal vertiports at population centers, with existing infrastructure of three airports, roads and rail links in the metropolitan area demonstrated the inevitable airspace management issues.…”
Section: Integration Of Civil Vtol Into a Metropolitan Or Regional Trmentioning
confidence: 99%
“…There are substantial future challenges related to sustaining and improving efficient, cost-effective, and environmentfriendly transportation options for urban regions. A recently completed study by NASA and Stanford University investigated the feasibility of a rotorcraft solution for future urban transportation (Melton et al, 2014;Sinsay et al, 2012). Such an aerial transportation system could ideally tackle concerns related to urbanization, transportation gridlock, and fossil fuel emissions.…”
Section: Green Vtol Transportation System: Hoppermentioning
confidence: 99%